Analisis Fungsi Media Massa Dalam Channel Youtube “Loloan Project” - Ni Putu Yunita Anggreswari; Sheila Novita Isnaeni (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
Mass communication is a process of delivering messages / information to the general public. Communication is conveyed through a container that is the mass media. Mass media as a place to convey messages / information from the mass communication process has 4 (four) mass media functions, namely the information function, the educational function, the entertainment function, and the influence function. The four media functions will be linked to the YouTube channel by the local community of Loloan, the "Loloan Project" in the mass media function. The researcher uses a descriptive qualitative research type, where the researcher will explain the result in the words. In the data collection stage, researchers used in-depth interviews with relevant informants, observation techniques as observers what elements of the mass media function contained in the youtube channel "Loloan project", then documentation techniques, namely research will present data in the form of photos / image from a video clip that the screenshoot researcher has. The results and discussion obtained from this research are where the researchers took several videos available on YouTube "Loloan Project" such as, comedy videos because of ML, comedy videos "when love rhymed" episodes 1 & 2, Loloan era Lame culture festival, drama studio pilot. "Election socialization", tradition of celebrating the birthday of the Prophet Muhammad in Loloan, and "Really Merdeka" official music video. The seven films that have been selected by researchers are associated with the concept of the function of the mass media. That the YouTube channel belonging to "Loloan Project" contains all of these elements.